LIFE-THREATENING MASSIVE THROMBOEMBOLISM AFTER LAPAROSCOPICSPLENECTOMY IN AN IDIOPATHIC THROMBOCYTOPENIC PATIENT - Uz, B.; Duzenci, D.; Atli, H.; Karakaya, B.; Onur, M.; Aygen, E. (Pergamon-Elsevier Science Ltd, 2014)
[Abstract Not Available]
5th International Eurasian Hematology Congress -- OCT 15-19, 2014 -- Antalya, TURKEY